ICT's and public sphere / Abd Rasid Abd Rahman - Abd Rahman, Abd Rasid (Centre for Media and Information Warfare Studies, 2009)
The development of the public sphere is important in order for ‘citizens’ to be able to participate fully in the democratic process. As pointed out by Dahlgren (1991:2), the concept of the public sphere can be regarded as a normative reference point and as a ‘visible indicator of our admittedly imperfect democracies’. Habermas (1989) famously in his work has made a clear reference to the decay of the public sphere as a result of extensive interests of private entities in public discourse. He saw that this could be problematic for organising open democratic expression in the public sphere